Studies of Adsorption-Desorption of Methylene Blue in a Fixed-Bed Reactor Filled with Cotton and Tanine Industry Waste (LACCEI, 2024)
In this paper, a laboratory scale fixed-bed reactor filled with cotton husk and quebracho chips was used to test the capabilities of these materials to be employed as dyes adsorbent materials in effluent treatment of textile industries. The adsorption-desorption processes of methylene blue on both adsorbents were studied and the number of effective cycles was determined in each case. Desorbent efficiency of three substances was evaluated: NaCl 0.1 M, ethanol 50% (V/V) and tap water. As much as three adsorption-desorption cycles were obtained in all cases.